The Reinforcement of Environmental Management for Wastewater Prevention and Treatment by Applying the Environmental Management Accounting Package Program - Khewpairee, Vararat; Kumprachum, Sommai (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
The purposes of this research were to study the Environment Management Accounting (EMA) of wastewater prevention and treatment by Local Administrative Organizations; to develop Environmental Management Accounting for Wastewater Pollution Prevention and Treatment (EnvAcc-WPT) package program; and to reinforce environmental management for the prevention and treatment of wastewater. This qualitative research used multi-stage random sampling, three samples were selected from the total of 50 Local Administrative Organizations in Samut Prakan province. Research instrutments included a questionnaire on program efficiency as well as preand post-tests for the program training. The content analysis technique was employed to analyze data in terms of percentage. Results revealed that: 1) Local Administrative Organization had never retained an account of EnvAcc-WPT. 2) EnvAcc-WPT package program V.1.0 and V.2.0 were developed, most of specialists and others assessed the efficiency of the package program as very good and good. 3) For the reinforcement of environmental management for wastewater prevention and treatment, most of the trainees attending the program acquired knowledge at a high level.